2017
DOI: 10.1021/acs.chemrestox.7b00025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DILI Predictive Hypotheses in Early Drug Development

Abstract: Drug-induced liver injury (DILI) is a leading cause of drug failure in clinical trials and a major reason for drug withdrawals. DILI has been shown to be dependent on both daily dose and extent of hepatic metabolism. Yet, early in drug development daily dose is unknown. Here, we perform a comprehensive analysis of the published hypotheses that attempt to predict DILI, including a new analysis of the Biopharmaceutics Drug Disposition Classification System (BDDCS) in evaluating the severity of DILI warning in dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 29 publications
3
54
1
Order By: Relevance
“…DILI gained much attention due to its importance in drug development along with its roles in failure or withdrawal of drug development [7]. The key issue related to treating DILI is to stop using the drug instantly that is a cause of liver injury in a dose-dependent fashion [8, 9]. The epidemiological studies of DILI showed that the dosage is a major determining factor of the risk that humans suffer from idiosyncratic adverse drug reaction [10].…”
Section: Introductionmentioning
confidence: 99%
“…DILI gained much attention due to its importance in drug development along with its roles in failure or withdrawal of drug development [7]. The key issue related to treating DILI is to stop using the drug instantly that is a cause of liver injury in a dose-dependent fashion [8, 9]. The epidemiological studies of DILI showed that the dosage is a major determining factor of the risk that humans suffer from idiosyncratic adverse drug reaction [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies showing that DILI patients have to face a mortality or liver transplantation rate of at least 5-10% [2,3]. Moreover, in past 50 years DILI was the leading single cause of drug failure during clinical phases and after market approval [4,5]. Therefore, regulatory authorities such as the Food and Drug Administration (FDA) recommended an industry guidance to detect DILI potentials of drug candidates as early as possible [6].…”
Section: Introductionmentioning
confidence: 99%
“…13 We have shown that the BDDCS can be useful in predicting the potential for antiepileptic drugs to cause cutaneous adverse reactions 14 and in predicting DILI. 15 Most recently, we have shown that in vitro measures of BSEP inhibition, alone and together with other efflux transporters, provides no better prediction of DILI than just avoiding BDDCS class 2 drugs. 16 BDDCS’s strong relationship between dose, metabolic susceptibility, solubility and idiosyncratic DILI highlights the potential benefits of BDDCS as a comparison matrix for DILI prediction.…”
Section: Introductionmentioning
confidence: 96%